2021
DOI: 10.3389/fgene.2021.682050
|View full text |Cite
|
Sign up to set email alerts
|

Cohort Analysis of 67 Charcot-Marie-Tooth Italian Patients: Identification of New Mutations and Broadening of Phenotype Expression Produced by Rare Variants

Abstract: Charcot-Marie-Tooth (CMT) disease is the most prevalent inherited motor sensory neuropathy, which clusters a clinically and genetically heterogeneous group of disorders with more than 90 genes associated with different phenotypes. The goal of this study is to identify the genetic features in the recruited cohort of patients, highlighting the role of rare variants in the genotype-phenotype correlation. We enrolled 67 patients and applied a diagnostic protocol including multiple ligation-dependent probe amplific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…The mutation hit‐rate of 33.3% compares favourably with other studies that have screened similar axonal CMT cohorts with larger NGS gene panels, which included the genes presently screened for. These studies have reported diagnostic yields of 20.7%–44.5% 17–23 . This confirms that a substantial proportion of CMT2 cases are caused by a relatively small number of genes 4 …”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The mutation hit‐rate of 33.3% compares favourably with other studies that have screened similar axonal CMT cohorts with larger NGS gene panels, which included the genes presently screened for. These studies have reported diagnostic yields of 20.7%–44.5% 17–23 . This confirms that a substantial proportion of CMT2 cases are caused by a relatively small number of genes 4 …”
Section: Discussionsupporting
confidence: 64%
“…These studies have reported diagnostic yields of 20.7%-44.5%. [17][18][19][20][21][22][23] This confirms that a substantial proportion of CMT2 cases are caused by a relatively small number of genes. 4 The most frequently involved genes were GJB1 (11.7%), MPZ (5%) MFN2 (5%), DNM2 (3.3%) and LRSAM1 (3.3%).…”
Section: Discussionmentioning
confidence: 52%
“…Mutations in KIF1A are linked to epilepsy, hereditary spastic paraplegia [a rare gait disorder caused by axonal defects or axonal degeneration in the spinal cord ( 53 55 )], and the peripheral neuropathy Charcot-Marie-Tooth disease ( 56 ). We thus speculate that defects in PI(3,5)P 2 -regulated axonal PV transport may be linked to some of these rare inherited neurological disorders and peripheral neuropathies.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been transformed by the advent of NGS, where several disease-associated genes are tested in parallel. Nevertheless, the diagnostic rate of massive parallel sequencing tests described in the literature ranges from 4.6% to 93%, according to the analyzed cohort [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. In routine clinical practice, the NGS approach more realistically allows us to reach a genetic diagnosis in 30% of genetically undetermined patients when PMP22 duplication has been previously ruled out [ 32 ].…”
Section: Discussionmentioning
confidence: 99%